Deuterium MRS for In Vivo Measurement of Lipogenesis in the Liver - Gursan, Ayhan; Graaf, Robin A.; Thomas, Monique A.; Prompers, Jeanine J.; De Feyter, Henk M. (NMR in biomedicine, 2025)
ABSTRACT Hepatic de novo lipogenesis (DNL) plays a key role in the pathogenesis of several metabolic diseases that affect the liver. In humans, the detection of deuterium (2H) in triglycerides from very low density lipoprotein collected from blood after administration of deuterated water (D2O) is commonly used as an indirect estimate of hepatic DNL. Here, we tested in rats (1) the feasibility to detect 2H‐labeling directly in liver lipids in vivo by using noninvasive 2H MRS and (2) to what extent these results correlated with the gold standard measurement of DNL in excised liver tissue. To increase hepatic DNL, half of the animals (n = 4) underwent a 7‐week dietary intervention in which fructose was provided in drinking water. Deuterium MRS data were acquired from a single voxel placed in the liver. In vivo 2H MRS data showed 2H‐labeling in the combined peak of methyl and methylene resonances after 1 week of administrati NBM_70014 on of 5% D2O as drinking water. DNL was calculated using 1H and 2H NMR data acquired from extracted lipids of excised liver tissue. The 2H lipid level measured in vivo correlated with the ex vivo estimates of hepatic DNL (r = 0.81, p = 0.016). These results demonstrate the feasibility of direct detection of deuterium labeling in liver lipids using localized 2H MRS in vivo and indicate the potential of this approach to measure hepatic DNL. These initial observations provide a basis for the method to be translated and to develop noninvasive, quantitative measurements of hepatic DNL in humans. Deuterium magnetic resonance spectroscopy was performed in rat liver in vivo, after a loading period during which D2O was provided in drinking water. The deuterium from D2O labels newly synthesized lipids that were detected with single voxel 2H MRS in vivo in rats to provide a measure of liver lipogenesis. The in vivo results were validated by comparison with high‐resolution 2H NMR in lipid extractions from excised rat liver tissue.